Efficacy Of Lagenaria Siceraria (Mol) On Lipid Profile In Isoproterenol-Induced Myocardial Infarction In Wistar Rats - M.VIJAYAKUMARPh.D,; V.SELVIPh.D,; S.KRISHNAKUMARIPh.D, (International Journal of Pharma and Bio Sciences, 2010)
Aim of the study: The present study was designed scientifically to evaluate the cardioprotective potential of ethanolic extract of Lagenaria siceraria fruit (EELSF) on the basis of lipid profile in isoproterenol induced myocardial infarction in albino rat models. Methods: Lipid profile namely phospholipids cholesterol, triglycerides, free fatty acids and lipoprotein were assayed in both serum and heart tissue. Results: Significantly reduced the cholesterol, triglycerides, free fatty acids and phospholipids levels in heart of the cardiotoxicity myocardial infarcted rats. Lagenaria siceraria (Mol) fruits also increased the cholesterol, triglycerides, free fatty acids and phospholipids significantly in isoproterenol induced cardio toxic rats. In isoproterenol administered rats, LDL and VLDL fractions were increased significantly with a decrease in HDL cholesterol in serum. Oral administration of EELSF (125, 250 and 500 mg/kg body weight) significantly reverted the levels of almost all the selected parameters to near normal. Conclusion: The experiment thus concludes that Lagenaria siceraria (Mol) fruits possess cardioprotective effect on experimentally induced cardiotoxic myocardial infarcted rats.